The Effect of Hydrotherapy and Progressive Muscle Relaxation (PMR) on Cortisol Levels in Primigravida Pregnant Women - Zulaeha Amdadi; Sitti Mukarramah; Mardiana Ahmad (CV. Inara, 2023)
This study aims to measure cortisol levels in pregnant women who have intervened with Hydrotherapy and Progressive Muscle Relaxation to reduce anxiety in pregnant women in facing labor. This type of research uses quantitative with a quasi-experimental design, and a pretest-posttest approach with a control group [10]. The sampling technique used was purposive sampling so that a total sample of 30 respondents was obtained. Analysis of the data collected in the study was processed analytically with the T-Paired test and the Independent Test. The results of this study showed that the hydrotherapy and Progressive Muscle Relaxation group with Paired T test results worth P Value 0.017 = 0.05, meaning that there is no effect of hydrotherapy and Progressive Muscle Relaxation on cortisol levels. Hydrotherapy and Progressive Muscle Relaxation therapy are effective in reducing anxiety levels and cortisol levels in primigravida pregnant women in the face of childbirth.